Proper Kids Handling in the Light of Sunnah Nabawiyyah - Mohammed Abdul Qawi Mohammed Saleh (Aṭfāluna: Journal of Islamic Early Childhood Education, 2021)
The research aims to identify the concept of childhood and models of proper handling ofchildhood in education and error handling. The researcher used the descriptive-analytical method in describing the concept of childhood, analyzing the texts of the Prophetic hadiths, and devising the rules of proper dealing with children. This research consists of three demands and a conclusion, the first contains the basics of research, the second deals with the concept of childhood, and the third deals with three prophetictexts, and then the research conclusion with its findings and recommendations.